Utilization of Wastewater from Air Conditioner Circulation Systems for Clean Water Energy Efficiency and Industrial Equipment Maintenance - Subandi; Azalia, Ailsa; Shaffira, Mutia Rizkia; Pratiwi, Nurma (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
There is significant wasteful use of clean water for operating equipment during field and laboratory practice. Additionally, damage to laboratory equipment has been reported due to the use of untreated water. These issues, along with previous research on managing air conditioner (AC) wastewater at the Lampung State Polytechnic, form the basis for our initiative to utilize AC wastewater as a sustainable resource. Proper management of this abundant water source can support the operation and maintenance of laboratory equipment. The research findings demonstrate that circulating AC wastewater to operate a Soxhlet extraction system for 4.5 hours can reduce clean water consumption by 0.65 cubic meters, equivalent to a cost savings of IDR 43,200. Furthermore, the results indicate improved efficiency, effectiveness, and overall equipment performance when using AC wastewater compared to conventional methods. Contribution to Sustainable Development Goals (SDGs) SDG 6 – Clean Water and SanitationSDG 9 – Industry, Innovation, and Infrastructure:SDG 12 - Responsible Consumption and ProductionSDG 13 - Climate Action